Free Nutritional Meals Program (Mbg) in Indonesia: Human Development according to an Islamic Perspective (Sharia Economic Review on Aspects of Insaniyah Development) - Aji, Rizqon Halal Syah (SALAM: Jurnal Sosial dan Budaya Syar-i, 2025)
This study aims to analyze the Free Nutritious Meals (MBG) program from the scope of human capital development from an Islamic economic perspective. MBG, which was born from President Prabowo Subianto's government program, does not contradict Islamic teachings in the slightest. This is not only from an Islamic economic perspective but also from the spirit of implementing Pancasila values and the mandate of the 1945 Constitution. Moreover, world religions other than Islam also provide support for the MBG program according to their teachings, as do humanitarian institutions in the world. The research method used in this study is qualitative research with library research. With the accuracy of this methodology, its main focus is exploring the literature to provide strong reasons for theoretical and empirical facts. The results of this study confirm that the MBG program is under the principles of Islamic economics in Indonesia as outlined by the maqashid al-syariah taught by the Qur'an and strengthens the human capital development system (insaniah), especially Muslims who are in number the recipients of the tremendous benefits from the implementation of the program.Keywords: MBG; Indonesia; Human Capital; Islamic Economics; Maqashid al-Shariah